2018
DOI: 10.1126/science.aar2555
|View full text |Cite
|
Sign up to set email alerts
|

Imaging dynamic and selective low-complexity domain interactions that control gene transcription

Abstract: Many eukaryotic transcription factors (TFs) contain intrinsically disordered low-complexity sequence domains (LCDs), but how these LCDs drive transactivation remains unclear. We used live-cell single-molecule imaging to reveal that TF LCDs form local high-concentration interaction hubs at synthetic and endogenous genomic loci. TF LCD hubs stabilize DNA binding, recruit RNA polymerase II (RNA Pol II), and activate transcription. LCD-LCD interactions within hubs are highly dynamic, display selectivity with bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

59
872
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 828 publications
(934 citation statements)
references
References 55 publications
(71 reference statements)
59
872
3
Order By: Relevance
“…The biomimetic construction of liquid organelle‐like materials in vitro provides a simplified alternative to understand the pathological phase transition of diseased organelles, thus shedding lights on the understanding of mechanism of neurodegenerative diseases and cancers. Besides, microfluidic preparation of organelle‐like materials also provides a platform to the preliminary screening and rapid testing of small molecular drugs targeting for specific organelle diseases . The membraneless organelles inspired biomaterials therefore are of great clinical importance in both disease study and treatment.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…The biomimetic construction of liquid organelle‐like materials in vitro provides a simplified alternative to understand the pathological phase transition of diseased organelles, thus shedding lights on the understanding of mechanism of neurodegenerative diseases and cancers. Besides, microfluidic preparation of organelle‐like materials also provides a platform to the preliminary screening and rapid testing of small molecular drugs targeting for specific organelle diseases . The membraneless organelles inspired biomaterials therefore are of great clinical importance in both disease study and treatment.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…Hnisz et al have suggested a phase separation model of enhancer assembly and function. Direct tracking of enhancer binding factors by different live cell microscopic approaches revealed formation of interaction hubs and a highly dynamic binding behavior of these factors with often very short dwelling times (< seconds) (for review, see References 46 and 97). Notably, these studies record the dynamics of binding factors and not potential movements of enhancer sequences per se.…”
Section: Accessibility Of Tres By Tfs May Depend On the Active Or Silmentioning
confidence: 99%
“…The modular nature of the phase transition‐promoting segment also helps with phenotypic diversity and the manifestation of new phenotypes during evolution, since such segments can evolve independently of the biochemical function mediated by the rest of the polypeptide (Bornberg‐Bauer & Alba, ; Boke et al , ; Lees et al , ). This may possibly explain why many regulators such as transcription factors (e.g., Snf5) contain phase separation‐promoting segments (e.g., Q/N‐rich segments) independently of structured domains that perform specific biochemical function such as DNA binding (Chavali et al , 2017a; Chong et al , ; Sabari et al , ). It is known that cell‐to‐cell variation in protein abundance of such regulators can lead to differential activation of downstream regulatory networks and drive the phenotypic differences in an isogenic population (Jothi et al , ; Halfmann et al , ; Holmes et al , ; Gemayel et al , ).…”
Section: Discussionmentioning
confidence: 99%